EFFECT OF SIC ON WEAR RESISTANCE OF HIGH ENTROPHY ALLOY COMPOSITE COATING AL70(FE-CR-NI)(30-X)(SIC)X WITH AISI 1018 SUBSTRATE BY MECHANICAL ALLOYING METHOD - Saragih, Yosua
The need for low carbon steel in the world increases every year. This happens because low carbon steel has various advantages of mechanical properties, especially good technological properties. This makes low carbon steel widely used in various structural applications, one of which is coal boilers. However, its soft nature actually makes low carbon steel have poor wear resistance so that it is limited to be used in several applications, especially applications that involve wear. In an effort to improve the wear resistance of low carbon steel, in this study, a coating process was carried out with AISI 1018 steel as a substrate with a coating component, namely composite coating Al70(Cr-Fe-Ni)(30-x)(SiC)x with X being the atomic percentage of SiC used. This study uses variations in the percentage of SiC of 0%, 10%, and 15% which are then given the codes 0SiC, 5SiC, 10SiC and 15SiC. The processing chosen in this coating is mechanical alloying (MA). MA was chosen because of several advantages such as being able to combine two or more elements that have different physical properties and chemical properties, as well as the ease of the process. This study evaluates the resulting phases, observations of the coating layer, evaluates the wear resistance of the coating layer for the three variations of the selected parameters. The samples produced through this method were successfully coated although from micro observation using SEM identified that there were still cracks and porosity in the coating. The results of the air jet erosion wear test with alumina erodent showed a smaller mass loss value at a larger percentage of SiC with an average mass loss at 0 SiC of 21,7 mg, at 10 SiC of 14.3 mg, and at 15 SiC of 21,7 mg. In addition, this result is also confirmed by the appearance of the eroded surface with a coarser topographic contour at 15 SiC followed by 10 SiC and the smoothest at 0 SiC which illustrates that more particles are deposited at a smaller SiC composition. In the pin on disc test, a greater mass loss was obtained at 15% SiC percentage followed by 10% SiC percentage and finally 0% SiC at 15.1 g, 14.15 mg, 9.85 mg respectively. This is also confirmed by the appearance of wear tracks that are deeper at 0 SiC and shallower at 15 SiC which illustrates better durability at higher SiC percentages.